2021
DOI: 10.1038/s41523-021-00291-z
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of B cells and lymphocyte clusters as a predictor of triple-negative breast cancer outcome

Abstract: While tumor infiltration by CD8+ T cells is now widely accepted to predict outcomes, the clinical significance of intratumoral B cells is less clear. We hypothesized that spatial distribution rather than density of B cells within tumors may provide prognostic significance. We developed statistical techniques (fractal dimension differences and a box-counting method ‘occupancy’) to analyze the spatial distribution of tumor-infiltrating lymphocytes (TILs) in human triple-negative breast cancer (TNBC). Our results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…In concordance with H&E sTILs, the vast majority of immune markers is enriched in stromal compartments of BC [74][75][76]. Indeed, T cells (CD3+, CD4+ or CD8+), B cells (CD20+) and macrophages (CD68+) are commonly found in stroma [62,63,73,77]. However, tumoral compartments seem to be more infiltrated by T cells (CD3+, CD8+) and NK cells (CD56+) [62,73,77,78].…”
Section: Intratumoral Spatial Heterogeneity: Regions Of Interest Tiss...supporting
confidence: 52%
See 1 more Smart Citation
“…In concordance with H&E sTILs, the vast majority of immune markers is enriched in stromal compartments of BC [74][75][76]. Indeed, T cells (CD3+, CD4+ or CD8+), B cells (CD20+) and macrophages (CD68+) are commonly found in stroma [62,63,73,77]. However, tumoral compartments seem to be more infiltrated by T cells (CD3+, CD8+) and NK cells (CD56+) [62,73,77,78].…”
Section: Intratumoral Spatial Heterogeneity: Regions Of Interest Tiss...supporting
confidence: 52%
“…This is more apparent for B cells, as 75% of density differences is attributed to ROI examination within a slide. Besides this, B cells seem to be distributed in TIME independently of their stromal density [73].…”
Section: Intratumoral Spatial Heterogeneity: Regions Of Interest Tiss...mentioning
confidence: 90%
“…The complex interactions among immune and tumor cells are crucial for tumor progression [ 29 ]. A recent study reported that lymphocyte clusters (LCs), like TLSs, are closer to tumor cell islands in patients with a good outcome, with a decrease in the LC size with decreasing distance to tumor cell islands [ 30 ]. Thus, it is crucial to identify the clinicopathological impact of TLSs in BCa.…”
Section: Discussionmentioning
confidence: 99%
“…High densities of TS-infiltrating CD4 + T cells favored DSS of non-small-cell lung carcinoma patients, whereas their frequency in the tumor islands did not have any effect on DSS [ 72 ]. In contrast, an increased frequency of tumor island-associated CD3 + T cells was linked to improved relapse-free survival in triple negative breast cancer [ 73 ]. Here, we showed that in contrast to IET-infiltrating cDC1s, a higher density of TS-associated cDC1s was significantly correlated with prolonged DFS.…”
Section: Discussionmentioning
confidence: 99%